Mathematics in the context of fuzzy sets: basic ideas, concepts, and some remarks on the history and recent trends of development - Sostaks, Alexander (Mathematical Modelling and Analysis, 2011)
The main aim of this paper is to discuss the basic ideas and concepts of the so called ‘Fuzzy Mathematics’ and to give a brief survey of the history and of some trends in recent development of mathematics and its applications in the context of fuzzy sets. As a potential reader we imagine a mathematician, who is not working in the field of ‘fuzzy mathematics’, but wishes to have some idea about this vast field in modern science.